Kajian Penggunaan Perabot Jalan Raya Dalam Mengurangkan Kemalangan Jalan Raya Di Selangor, Malaysia - Harun, Muhammad Hilmi; Omar, Roshartini (Research in Management of Technology and Business, 2022)
Road accidents contribute to the increase in the number of deaths in Malaysia and one of the factors is due to road furniture not working and effective on the road. Although the number of accidents has decreased lately, accident cases are still increasing and measures to improve the effectiveness of road furniture need to be emphasized. Various issues and complaints related to the ineffective use of street furniture by road users include street lights, signboards, street humps, AES cameras, delineator posts, and road studs. The objective of this study is to identify the types of street furniture. cause road accidents, study the effectiveness of the use of road furniture in reducing road accidents, and describe the steps that can be taken to increase the effectiveness of the use of road furniture in reducing road accidents. The scope of the study involves assistant road engineers JA29, road engineers J41, and road contractors in Sepang who are experienced in the handling and maintenance of road furniture. The qualitative approach was used by interviewing 3 respondents from different agencies namely JKR, PBT, and Jurumart Sdn Bhd through the Google Meet application, and data were analyzed using the content analysis method by scheduling to compare statements between respondents. The results of the study found the types of road furniture that frequently cause road accidents which if the road furniture is not maintained properly, it will contribute to the possibility of road accidents. While the effectiveness of the road furniture studied, namely street lights, signboards, road humps, AES cameras, delineator posts, and road studs can significantly reduce the number of road accidents. Furthermore, measures that can be taken to increase the effectiveness of the use of road furniture with modern technology such as LED, Reflective Strips, and Intelligent Transport System can reduce road accidents, handling, and maintenance of road furniture in reducing road accidents.